Childbirth Experience and Its Related Socio-Demographic Factors in Mothers Admitted to Postpartum Ward of AL Zahra Hospital of Rasht City, (Iran) - Parisa Zamani; Tahereh Ziaie; nasrin Mokhtari Lakeh; ehsan Kazemnejad Leili (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2019)
Background and Objectives: A positive childbirth experience is associated with sense of control, power, and satisfaction in mother, which affects mother’s sexual activity with her newborn, her sexual activity and her planning for future pregnancies. This study aimed to determine the childbirth experience and its related socio-demographic factors.